2001
DOI: 10.1161/01.cir.103.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin in Acute Rheumatic Fever

Abstract: Background-Acute rheumatic fever (ARF) remains the leading cause of acquired heart disease in children worldwide. No therapeutic agent has been shown to alter the clinical outcome of the acute illness. Immunological mechanisms appear to be involved in the pathogenesis of ARF. Intravenous immunoglobulin (IVIG), a proven immunomodulator, may benefit cardiac conditions of an autoimmune nature. We investigated whether IVIG modified the natural history of ARF by reducing the extent and severity of carditis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 27 publications
0
32
0
2
Order By: Relevance
“…In summary, several articles reported cases of progressive valve dysfunction during follow-up [3,7,15,16]. Others reported improvement and even resolution [2,14,[17][18][19][20][21].…”
Section: Outcome Of Subclinical Carditis In Arfmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, several articles reported cases of progressive valve dysfunction during follow-up [3,7,15,16]. Others reported improvement and even resolution [2,14,[17][18][19][20][21].…”
Section: Outcome Of Subclinical Carditis In Arfmentioning
confidence: 99%
“…In a proportion of patients with ARF, pathological valvular regurgitation that is not evident clinically can be seen on echocardiography [2][3][4][5][6][7]. This has been termed subclinical carditis (SCC).…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports of using immunomodulators like intravenous gamma globulin in high doses for the treatment of rheumatic carditis. The results, however, are not encouraging [14].…”
Section: Dosage Schedulementioning
confidence: 89%
“…It was found that IVIG did not alter the clinical course or lead to reduction in echocardiographic evidence of acute valvular disease or chronic cardiac damage one year later [29]. We have also considered a larger, international study with echocardiographic endpoints to re-evaluate the potential benefits of corticosteroids [30] and other newer anti-inflammatory agents on acute rheumatic carditis and longer term cardiac outcome.…”
Section: Cardiac Assessment In Arfmentioning
confidence: 99%